"Methods of media war in terrorist organizations and mechanisms used to address them Analytical theory study on the so-called "Islamic State Organization - Al Zayadi, Lotfi Mohammed (Journal of Humanities & Social Sciences, 2018)
The purpose of this research is to study media war and how it is used by terrorist organizations by defining the conditions of its establishment, highlighting its mechanisms and analyzing its most important features among terrorist organizations in general and the so-called ‘Organization of the Islamic State’ in particular. The reason for this concern is the growing importance of the media war and the fundamental and pivotal role played by traditional and modern media, or the so-called new media and social networking sites (Twitter, Facebook, YouTube. . . ) in attracting the Mujahideen and spreading their ideas and beliefs and resorting to these means to coordinate criminal operations committed by terrorist organisations within the hotbeds of tension, as well as within peaceful countries. In order to conduct a rigorous scientific analysis of communication and media strategy used by the so-called ‘Organization of the Islamic State’ and to study ways and means of its embodiment as well as propaganda content disseminated and published by this organization, we used the analytical descriptive method, which descripes "what exists" with respect to situational variable , and adopted quantitative and qualitative analysis mechanisms and tools. After explaining and analyzing the components and tools of the adopted communication and media strategy , we find that the so-called "Organization of the Islamic State" completely controls the communication process and mixes between traditional and modern means of communication and media and uses the symbolism at the level of form and content through the selection of dates and the use of religious references to justify criminal acts and to give evidence on credibility. Our research concluded that addressing the communication and media war waged by terrorist organizations in general and the so-called "Organization of the Islamic State" in particular requires tightening controls on the means of communication, media and suspicious social networking sites and intensifying international communication and media cooperation especially with countries affected by terrorist crimes , as well as organizing awareness campaigns on the dangers of the terrorist media contents aimed at young men and children and the inclusion of the "Media Education" course as a compulsory subject in schools and secondary institutes to prepare a generation capable of dealing positively and intelligently with traditional and particularly modern media.